'For the sake of science and country': the Ross Sea party 1914–1917. (July 2015) - Harrowfield, David L.
ABSTRACT In December 1913 Sir Ernest Shackleton released a prospectus and announced The Imperial Trans-Antarctic Expedition. His goal was to undertake the first crossing of Antarctica from the Weddell Sea via the polar plateau to McMurdo Sound on the Ross Sea. The journey had already been attempted by Wilhelm Filchner whose ship Deutschland, had become beset in the Weddell Sea ice for nine months in 1912. Shackleton aimed 'to make all possible scientific observations on [the Trans-Antarctic] journey; to carry on similar work by parties operating from the two bases on the Weddell and Ross Seas [and] to carry on scientific work, and travel unknown portions of the coastline, by the two ships of the expedition'(Shackleton 1913: 3). With Endurance a continental crossing party of six led by Shackleton would begin from the Weddell Sea and a supporting depot laying party led by Nimrod veteran Lieutenant Aeneas L.A. Mackintosh RNR, with the auxiliary barquentine Aurora based in McMurdo Sound. Unbeknown to each party, both experienced problems beyond their control. Endurance was holed and sank in the Weddell Sea and Aurora locked in ice, although damaged, reached New Zealand. Here the ship was repaired and then undertook a relief expedition with Shackleton as a passenger, to McMurdo Sound. In spite of these major setbacks each party conducted valuable scientific observations. When Shackleton published his book South (Shackleton 1919) on the expedition, compiled with New Zealand journalist and friend Edward Saunders, with exception of accounts on the Ross Sea party sledging and drift of the ship Aurora, no recognition was given to work undertaken by the four Ross Sea party scientists and an assistant. Later publications have focused on the depot-laying, while books on Antarctic science have largely overlooked the science undertaken. The purpose of this paper is to make this better known, and to give credit to the four scientists involved. The science conducted although primarily concerned with meteorological observations, also covers limited glaciological observations including the ablation of lake ice, solution of glacier ice in salt water, tidal recordings, collection of zoological and other specimens, along with the use of improvised equipment to undertake observations. The science achieved was secondary to the field work. The Ross Sea party science was done however, under conditions not normally conducive for such field work with health issues a major contributing factor. A lack of funding, equipment, personality problems, concern for Aurora and crew, uncertainty of Shackleton's Antarctic crossing and their own relief, led to depression, sleeplessness and insomnia.